Child Pornography and Child Abuse in Cyberspace (Journal of Legal Studies, 2018)
In the course of time, it has been demonstrated that the Internet is a vulnerable system, and this aspect, combined with the advantages it offers (storage, processing and transmission of huge amounts of data, accessibility, ease of use, distance-independence, the possibility of applications in the business field), have resulted in a favourable context for criminal activities, triggering the emergence of a new criminal phenomenon – cybercrime.